Поховання зрубної спільноти з булавами - Житников, В.Г.; Циміданов, В.В. (Археологія, 1999)
У статті розглянуто поховальні комплекси зрубної культури, які містять булави. Робиться висновок, що у розвиненій зрубній культурі поховання з булавами не менш репрезентовані, аніж серед комплексів покровського типу. В статье рассматриваются погребения с булавами срубной культурно-исторической общности, вводятся в оборот новые комплексы, содержащие данную категорию погребального инвентаря. Затрагивая проблему выделения памятников покровского типа (культуры), автор ставит под сомнение утверждение, согласно которому с исчезновением памятников покровского типа исчезают и погребения с булавами среди захоронений срубной общности. The paper discusses the burials with maces attributed to the Zrubna Cultural-Historical Community and introduces the new burial complexes with the above category of burial stock. The authors have touched on the problem of identification of archaeological sites of Pokrovsky type (culture); they also have cast some suspicion on the contention that the burials with maces among the burials of the Zrubna Community disappeared along with the disappearance of the sites of Pokrovsky type.